Chapter Il viaggio fantastico di de Chirico, Savinio, Landolfi - Spignoli, Teresa (Studi e saggi, 2021)
The intervention addresses three metaphysical and fantastical exemplary works from the twentieth century - Ebdòmero, La partenza dell'Argonauta, Il Mar delle Blatte - in which the theme of travel finds expression through different textual models. In the first case, De Chirico uses the archetypical model of Ulysses' journey against a background of fantastic metaphysical imagery. In the second Savinio creates a parodistic rewriting of the Argonautiche by Apollonio Rodio - the mythical trip par excellence, while in the third (Il mar delle blatte) Landolfi recalls the characters of Salgari's adventure novels. All three texts represent imaginary travels towards an unreachable elsewhere, symbolically represented by a paradisiacal Island, lost and dreamt of also by the sailor Pessoa.